Impact of COVID‐19 pandemic on patients with obstructing urinary stones complicated by infection. Issue 4 (13th March 2022) - Herzberg, Haim; Savin, Ziv; Lasmanovich, Rinat; Marom, Ron; Ben‐David, Reuben; Mano, Roy; Yossepowitch, Ofer; Sofer, Mario
Abstract: Objective: To assess the influence of COVID‐19‐imposed life changes on presentation and outcomes of patients with obstructing urinary stones complicated by infection. Patients and methods: All patients presenting with obstructing urinary stones and infection 1 year before the pandemic (March 2019 to February 2020; n  = 66) and 1 year since its onset (March 2020 to February 2021; n  = 45) were enrolled. Demographics, clinical presentation, laboratory panel, stone characteristics and outcomes were compared between groups. Univariate and multivariate logistic regression models were performed for analysis. Results: The COVID‐19 period was characterised by younger patients, female predominance, higher temperature at presentation and more bilateral obstructing stones ( p  < 0.05). The admission rate to intensive care units was double that of the pre‐pandemic period, whereas time between diagnosis and treatment was similar. The univariate analysis revealed higher rates of severe sepsis (odds ratio [OR] = 3, p  = 0.01), systemic inflammatory response syndrome (SIRS) ≥ 2 (OR = 2.9, p  = 0.01) and risk, injury, failure, loss of kidney function and end‐stage kidney (RIFLE) criteria ≥ 1 (OR = 2.2, p  = 0.04) in the pandemic period group. The multivariate analyses revealed the COVID‐19 period as being the sole variable associated with severe sepsis (OR = 3.1, p  = 0.02), SIRS ≥ 2 (OR = 3.8, p  = 0.005) and RIFLE ≥ 1 (OR = 2.6, p  = 0.05). Conclusions: The pandemic period was characterised by a worse clinical state at presentation of patients with obstructing urinary stones complicated by infection, probably reflecting delay in arrival to emergency services.